Teachers life stories: recovering, rebuild¬ing and re-signifying identities (Praxis Educativa, 2012)
The article shows the process of reconstructing the life stories of both a male and female elementary school teacher, during a nearly fifty-year career which was the focus of the investigation. In this process, different perspectives of analysis have been driven: historical, social, educational, curricular, political and personal, in a complex journey and from a kaleidoscopic view of teacher identities. The analysis and re-construction of life stories have allowed display some cores or nodes or identity nets that have sustained and set the personal and professional lives. At the same time they are and become the drivers or motors of change and reflection in retrospective.
Keywords: teaching career; life histories; teaching identities; biographical-narrative perspective